Book Review: Simone Gigliotti, Jacob Golomb and Caroline Steinberg Gould (ed.), "Ethics, art and representations of the Holocaust: essays in honor of Berel Lang" - Allwork, Larissa (Sage, 2017)
Book review for the 'Journal of Contemporary History'